The Role of Public Management Information System in The Organization of Nagari Government III Koto Aur Malintang Government - Putri Oktaviane, Diga; Bila, Aziza; Assyahri, Wahib (Iapa Proceedings Conference, 2023)
A management information system is an absolute necessity in every organizational body. Having a management information system is very helpful in carrying out the work processes of the organization or agency itself so that in the end it can work effectively, efficiently and as expected. The purpose of this research is to determine the role and efforts made by nagari in implementing digital nagari, this is done to increase the capability of nagari apparatus in providing services to the community. This research uses a qualitative method where the results obtained are descriptive data written based on sources obtained from books, journals, articles and the Nagari website. From the research carried out, it was found that the results of the discussion were that the use of information and communication technology must also be followed by the nagari government because the nagari is the spearhead of services that directly relate to the community so that work becomes more effective, efficient and able to fulfill the principles of information disclosure that have been mandated by the Openness Law. Public Information Number 14 of 2008. Efforts that can be made by nagari are by creating an official nagari website and an online sipena application which is useful for providing information effectively and efficiently to the public.